Land-Use Type as a Driver of Large Wildfire Occurrence in the U.S. Great Plains - Victoria M. Donovan (Remote Sensing, 2020)
Wildfire activity has surged in North America’s temperate grassland biome. Like many biomes, this system has undergone drastic land-use change over the last century; however, how various land-use types contribute to wildfire patterns in grassland systems is unclear. We determine if certain land-use types have a greater propensity for large wildfire in the U.S. Great Plains and how this changes given the percentage of land covered by a given land-use type. Almost 90% of the area burned in the Great Plains occurred in woody and grassland land-use types. Although grassland comprised the greatest area burned by large wildfires, woody vegetation burned disproportionately more than any other land-use type in the Great Plains. Wildfires were more likely to occur when woody vegetation composed greater than 20% of the landscape. Wildfires were unlikely to occur in croplands, pasture/hay fields, and developed areas. Although these patterns varied by region, wildfire was most likely to occur in woody vegetation and/or grassland in 13 of 14 ecoregions we assessed. Because woody vegetation is more conducive to extreme wildfire behaviour than other land-use types in the Great Plains, woody encroachment could pose a large risk for increasing wildfire exposure. Regional planning could leverage differential wildfire activity across land-uses to devise targeted approaches that decrease human exposure in a system prone to fire.